The Effect Of The Sun Roof Of Global Warming - Indri Dayana (Education Achievement: Journal of Science and Research, 2021)
A research on the study on The Effect Of The Sun Roof Of Global Warming in the laboratories of Physics Academy Maritim Belawan on August 24, 2016 - September 7, 2016. Materials used in this study are: 7 color plastic mica and 7 pieces of rubber bands, The tools used in this research are 7 and 2 pieces of fruit thermometer stopwatch. From this research, can inform the public, should buy or wear a canopy roof tiles and white houses, green, and purple because, from the research results, the three colors have a temperature with low radiation. So as to reduce global warming.